Minimum quality standards and novelty requirements in a one-shot development race - Jacek Prokop; Pierre Regibeau; Katharine Rockett (Kiel Institute for the World Economy (IfW), 2009)
The authors examine the timing and quality of product introduction in an R&D stopping game, where they allow for horizontal and vertical differentiation in the product market. They observe that discontinuous changes in introduction dates can occur as firms' abilities as researchers change. Further, the authors observe differences in the social optimality of entry patterns depending on the underlying research abilities of the firms. Minimum quality standards and novelty requirements can play a role in correcting these suboptimal patterns of entry. The authors find that increasing the novelty requirement does not necessarily increase either the profits or, consequently, the investment levels of the initial innovator, contrary to much of the cumulative innovation literature. When the research abilities of the firms differ, either the high ability firm or the low ability firm may be the first mover. Policy interventions have much more ambiguous welfare effects in this asymmetric case, as they can change the order of entry.
Keywords: L15; L16; O31; O33; O34; 330; Innovation; minimum quality standards; novelty requirements; stopping game; Industrielle Forschung; Produktqualität; Normung; Suchtheorie; Innovationswettbewerb; Spieltheorie; Theorie